Mother’s Knowledge on Diarrhea in Toddlers at Sangkunur Community Health Center - Sianipar, Connie (Caring: Indonesian Journal of Nursing Science, 2021)
Diarrhea is the second leading death cause in toddlers after pneumonia. It is a disease that often occurs in seemingly healthy toddlers. In Indonesia, every child has 1.6-2 times diarrhea episodes per year. This study aims to find out how thoroughly the mother's knowledge of diarrhea in toddlers at Sangkunur Community Health Center in 2019. This research was conducted by collecting data through a research questionnaire. The sample is 33 mothers who brought their toddlers to the community health centre. The result is most mothers have poor knowledge of diarrhea in their toddlers. Twenty-two respondents (66.67%) had a good understanding of the diarrhea definition. Twenty-three respondents (67.70%) had a poor understanding of diarrhea causes. Twenty-five respondents (75.76%) had a poor understanding of diarrhea signs and symptoms. Twenty-two respondents (66.67%) had a poor understanding of diarrhea prevention, and 29 respondents (87.88%) had a poor understanding of diarrhea management. The conclusion is community health centres should be more active in providing counselling about diarrhea and visit people's houses to give further information regarding diarrhea. Â